Extensão Universitária & Saúde Ambiental - Santana, Flávia Ribeiro (2019)
Due to the relevance of the University Extension, inseparable with teaching and researching, to contribute to the development of the Environmental Health area in the sense of greater social significance, and the need to build a database that references the qualification, valorization and strengthening of the extension activity in the area, this work is dedicated to present the research whose objective was to investigate the extension activities in Environmental Health registered in the Information System of Extension (SIEX) of the Federal University of Uberlandia (UFU), from 2010 to 2017, characterizing them and conducting an analysis of the theoretical content of their projects by approaching the prerogatives of the University Extension according to the National Extension (PNEXT) and Environmental Health with an ecosystem approach to health. The methodological efforts were focused on a predominantly qualitative approach, also using quantitative data, document research and content analysis. According to the survey, 103 extensionist actions were carried out in Environmental Health during the investigation period, with the majority being 'projects' and 'events' modalities. The most worked themes were 'prevention of chronic diseases', 'herbal and medicinal plants' and 'sanitation'. Several cities were contemplated, totaling more than 170000 (one hundred and seventy thousand) participations, most of them belonging to the academic community. The Institute of Geography was the unit that most promoted actions and, from the work teams, the administrative technicians in education were the ones who participated the least. Most of the actions were carried out with partnerships and using participatory methodologies with planning and qualification of the teams, situational diagnoses and various educational techniques and tools. In the theoretical content of the projects analyzed, the prerogatives of the National Extension Policy and an ecosystem health perspective fell short of expectations. For the evolution of the University Extension in Environmental Health in harmony with the guidelines of the PNEXT and an ecosystem approach in health, and to guarantee a significant presence of the universities in their local contexts, it is necessary to abandon definitively the traditionalist approach of extension in Environmental health. We hope that from the reflection on the work accomplished it will be possible to glimpse new paths for the extension work in Environmental Health and for the University Extension as a whole.